Cataract and Refractive Surgery - Nasir, Jamshed (Pakistan Journal of Ophthalmology, 2018)
The last quarter of a century showed tremendous innovations and improvements in medical science in general and Ophthalmology in particular. The ophthalmic conditions once thought to be dreadfully blinding are now tackled effectively after better understanding of the disease process. These improvements involve practically all areas in Ophthalmology from anterior to posterior segment, orbital to adnexal sub specialty of ophthalmology where better understanding of the subject has lead to better management, revolutionizing the treatment plan of the disease and the patients.